2008
DOI: 10.1109/tvcg.2007.70429
|View full text |Cite
|
Sign up to set email alerts
|

Practical Box Splines for Reconstruction on the Body Centered Cubic Lattice

Abstract: Abstract-We introduce a family of box splines for efficient, accurate, and smooth reconstruction of volumetric data sampled on the body-centered cubic (BCC) lattice, which is the favorable volumetric sampling pattern due to its optimal spectral sphere packing property. First, we construct a box spline based on the four principal directions of the BCC lattice that allows for a linear C 0 reconstruction. Then, the design is extended for higher degrees of continuity. We derive the explicit piecewise polynomial re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
91
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(91 citation statements)
references
References 25 publications
0
91
0
Order By: Relevance
“…The extremal properties in terms of surface-to-area ratio of the hexagonal (in 2D) and truncated octahedral (in 3D) tessellations imply that they may serve as optimal tool for achieving data compression [57]. Another similarity of these two tessellations is related to their topologically stability with respect to infinitesimal perturbations to the position of the lattice points [58].…”
Section: Introductionmentioning
confidence: 99%
“…The extremal properties in terms of surface-to-area ratio of the hexagonal (in 2D) and truncated octahedral (in 3D) tessellations imply that they may serve as optimal tool for achieving data compression [57]. Another similarity of these two tessellations is related to their topologically stability with respect to infinitesimal perturbations to the position of the lattice points [58].…”
Section: Introductionmentioning
confidence: 99%
“…The advantage of using Z d as the lattice is that the choice of the d axes is straightforward, and that each of the d directional blurs is simple: for all x ∈ R d , x can be blurred with points of the form x ± u k . Meanwhile, it has been observed that box splines on the body-centered cubic lattice A * 3 can be expressed using four projected axes of the 4D hypercube [19]. We generalize this observation below.…”
Section: Blurringmentioning
confidence: 68%
“…A * d is affinely equivalent to the Kuhn triangulation [25], which partitions a unit cube into tetrahedra. Sampling and reconstructions on the BCC lattice have been studied previously by Entezari et al [18,19]. In the computer graphics community, A * d has been used by Perlin [33] for generating high-dimensional procedural noise, and by Kim [23] for interpolating high-dimensional splines.…”
Section: Lattices and The Permutohedral Latticementioning
confidence: 99%
“…Nürnberger et al 2005;Rössl et al 2004;Sorokina and Zeilfelder 2007) or in trivariate box splines (see e.g. Entezari and Möller 2006;Entezari et al 2008Entezari et al , 2009Kim et al 2008;Remogna 2010b,c).…”
Section: Introductionmentioning
confidence: 99%